Pendampingan Pengisian SPT Tahunan Wajib Pajak Orang Pribadi di Wilayah Sidoarjo - Zahra Gunawan; Riska Ainur Rosyida; Achmad Wicaksono (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The purpose of this service is to improve the compliance of Individual Taxpayers (WPOP) in reporting Annual Tax Returns in the Sidoarjo area through a mentoring program. The method used includes education and direct assistance carried out by tax volunteers from the University of Nahdlatul Ulama Sidoarjo, with a technical guidance approach for filling out tax returns and tax socialization. The results of the service showed a significant increase in the number of WPOPs who reported their tax returns on time and with more accurate data. This assistance also succeeded in reducing tax return filling errors and increasing community understanding of tax obligations. The impact on the community includes increased tax literacy, ease in the reporting process, and increased awareness of the importance of taxes for development. This program is expected to become a sustainable model to support tax compliance in other areas